1983
DOI: 10.1159/000238205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceftizoxime, a New Cephalosporin Antibiotic, on Binding of Bilirubin to Human Serum Albumin

Abstract: An investigation and comparison of the competitive effect of ceftizoxime, a new cephalosporin, and other β-lactam antibiotics on in vitro binding of bilirubin to human serum albumin showed that at a normal range of serum albumin (3.48 g/di) and bilirubin (0.94 mg/dl) in healthy infants, free bilirubin did not increase in the presence of any of the test antibiotics at concentrations up to 640 μg/ml. When the albumin concentration was decreased to one-fifth of the normal human range, only ceftizoxime caused no b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…These varia tions, proportionally more important for low concentrations of ceftriaxone, may be explained by a higher protein binding at these concentrations [15] and/or by an easier displacement from weakly binding sites of serum albumin. Importance of competition between bilirubin and anti biotics might depend on the large extent of protein binding [11] and our results might be explained by the high binding of ceftri axone (83-96%) [15]. However, this fea ture is not the only one: Stutman et al [16] reported that cefoperazone is bound up to 90% to serum albumin and exhibits a less er bilirubin-displacing effect than moxalactam for which binding is about 60%.…”
Section: Discussionmentioning
confidence: 72%
“…These varia tions, proportionally more important for low concentrations of ceftriaxone, may be explained by a higher protein binding at these concentrations [15] and/or by an easier displacement from weakly binding sites of serum albumin. Importance of competition between bilirubin and anti biotics might depend on the large extent of protein binding [11] and our results might be explained by the high binding of ceftri axone (83-96%) [15]. However, this fea ture is not the only one: Stutman et al [16] reported that cefoperazone is bound up to 90% to serum albumin and exhibits a less er bilirubin-displacing effect than moxalactam for which binding is about 60%.…”
Section: Discussionmentioning
confidence: 72%
“…Ceftizoxime is a third-generation broadspectrum parenteral cephalosporin with ac tivity against a wide variety of gram-positive may be an advantage for hyperbilirubinémie infants with sepsis [2], It is excreted essential ly unchanged via the kidney [3], In prelimina ry studies, satisfactory clinical response to ceftizoxime was seen in 86-88% of septic neo nates [4,5], Satisfactory bacteriological re sponse ranged from 86 to 100% depending on the étiologie agent [4,5], This broad-spectrum antibiotic may prove to be an effective single agent for treating neonatal infections without any of the potential adverse effects of an ami noglycoside.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing unbound bilirubin con centration in blood by the drug-induced displacement from human serum albumin (HSA) causes bilirubin encephalopathy [1][2][3]. Caution must be exercised in admin istering these drugs to neonates having a strong binding capacity for HSA.…”
Section: Introductionmentioning
confidence: 99%